PERAN ORANG TUA SISWA SEKOLAH MENENGAH PERTAMA NEGERI 3 UKUI KELAS VIII TAHUN PELAJARAN 2021/2022 DALAM KEGIATAN PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN SECARA DARING AKIBAT PANDEMI COVID-19 - Khoirunnisa Khoirunnisa; Ni Putu Nita Wijayanti; Rusmanto Rusmanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study generally aims to determine the role of parents of State Junior High School 3 Ukui 8th grades students in the 2021/2022 academic year in online learning activities for Physical Education, Sports and Health due to the covid-19 pandemic. Thys type of research is descriptive research with a quantitative approach. The population in this study were all parents of students of State Junior High School 3 Ukui 8th grades for the 2021/2022 academic year, totaling 77 people. The data collection technique used in this research is to use an instrument in the form of a questionnaire which is distributed directly to the respondents. The analysis technique used is quantitative descriptive analysis which is stated in the form of percentage. The results of this study indicate that the role of parents of State Junior High School 3 Ukui 8th grades students in the 2021/2022 academic year in online learning activities for Physical Education, Sports and Health due to the covid-19 pandemic shows that they are in the Good category. With considerations based on the results of the research and discussion that have been presented, it can be concluded that the role of parents of State Junior High School 3 Ukui 8th grades students in the 2021/2022 academic year in online learning activities for Physical Education, Sports and Health due to the covid-19 pandemic is good. This is indicated by the percentage result of 70.1%.Keywords: The Role of Parents, Online Learning, Pandemic Covid-19.